0% found this document useful (0 votes)
7 views6 pages

Solution 1462434

Download as pdf or txt
Download as pdf or txt
Download as pdf or txt
You are on page 1/ 6

Solution

CLASS 10 MATHEMATICS

Class 10 - Mathematics
Section A
1.
(d) 7

5
,− 7

Explanation: p(x) = 25x2 - 49 = 0


= (5x - 7)(5x + 7) = 0
−7
∴ x = and 7

5 5

2.
(c) 0
Explanation: 0
3. (a) parallel
Explanation: Given: a1 = 6, a2 = 2, b1 = -3, b2 = -1, c1 = 10 and c2 =9​​
a1 = 6, a2 = 2, b1 = −3, b2 = −1, c1 = 10 and c2 = 9
a1 b1 −3 c1
Here a2
=
6

2
=
3

1
,
b2
=
−1
=
3

1
,
c2
=
10

9
c1
but c2
=
10

a1 b1 c1
∵ = ≠
a2 b2 c2

Therefore, the lines are parallel.


4.
(d) ±4
Explanation: ±4
5. (a) -504
n
Explanation: Sn = 2
× [2a + (n - 1)d]
a = 16, d = -4, and n = 21.
Sn = × [2(16) + (21 - 1)(-4)]
21

= 21

2
× [32 + 20× (-4)]
= 21

2
× [32 - 80]
= 21

2
× (-48)
Now, calculate the product:
= -21 × 24
= - 504
So, the sum of the first 21 terms of the given A.P. is -504.
6.
a+c
(d) 2

Explanation: If a, b and c are in A.P., then


b-a=c-b
2b = a + c
a+c
b= 2

7.
(d) 10
Explanation: The distance of the point P( -6,8) from the origin (0, 0)
−−−−−−−−−
2 2
= √(−6) + 8

−−−−−−
= √36 + 64
−−−
= √100

= 10

1/6
All the best
8. (a) 2 : 3
Explanation: Given: (x, y) = (1, 3), (x1, y1) = (-6, 10), (x2, y2) = (3, -8)
Let m1 : m2 = k : 1
m1 x2 + m2 x1
∴ x= m1 + m2

k×4+1×(1)
1= k+1

k + 1 = 4k - 1
⇒ k =
2

Therefore, the required ratio is 2 : 3


9.
(d) A is false but R is true.
Explanation: If the lines are coincident, then it has an infinite number of solutions.
The reason is clearly true.
10. (a) Both A and R are true and R is the correct explanation of A.
Explanation: Assertion 9x2 + 3kx + 4 = 0
D = b2 - 4ac
= (3k)2 - 4(9)(4)
= 9k2 - 144
For equal roots D = 0
9k2 = 144
k=± 12

k = ±4
Section B
11. α and β are zero of the polynomial:
p(x)=4x2-5x-1
a=4,b=-5,c=-1
5
So, Sum of the zeroes = α + β=- a
b
=
4
−1
Product of the zeroes = αβ= c

a
=
4

Now, α2β + αβ2 = αβ(α + β)


5 −1
= ( )
4 4

−5
=
16
.
12. 3x + 2y - 7 = 0 ....(i)
4x + y - 6 = 0 ....(ii)
From eqn. (ii)
4x + y - 6 = 0
4x + y = 6
y = 6 - 4 x ...(iii)
On putting this value of y in eqn. (i)
3x + 2(6 - 4x) - 7 = 0
⇒ 3x + 12 - 8x - 7 = 0
⇒ -5x + 5 = 0
⇒ 5x - 5 = 0
⇒ 5x = 5
⇒ x = 5/5
∴ x = 1

Substituting this value of x in (ii), we get,


4(1) + y - 6 = 0
⇒y=6-4×1
⇒y=6-4
⇒y=2

2/6
All the best
Hence, values of x and y of given linear equations are 1 and 2 respectively.
13. We have, (k+4) x2 + (k+1)x + 1= 0
Here a = (k+4), b = (k+1), c =1
⟹ D = b2 -4ac = (k+1)2 - 4 (k+4) (1)
= k2 +1 + 2k - 4k -16= k2 -2k -15
For equal roots, D = 0
⟹ k2 - 2k -15 = 0
⟹ k2 - 5k + 3k -15 = 0
⟹ k (k - 5) +3 (k - 5) = 0
⟹ (k+3) (k-5) = 0

Either k+3 = 0 or k-5 = 0


⟹ k = -3, 5

OR
Let first root of given quadratic equation be α
According to question second root = 3α
We know that
Sum of roots = − b

a
−b
α + 3α =
a
−12
⇒ 4α =
1

⇒ α = -3
Product of roots = c

a
−k
α × 3α =
1

3α = -k
2

Put the value of α


3 × (-3)2 = -k
k = -27
Section C
14. Let the given polynomial is p(x) =x2 + 7x + 7
Here,a = 1, b = 7, c = 7
∴ α, β are both zeroes of p(x)
−b
∴ α + β =
a
= -7.........(i)
αβ =
c

a
= 7 ...........(ii)
Now,
1 1 β +α
+ − 2αβ = − 2αβ
α β αβ

−7
= − 2 × 7
7

= -1 - 14
= -15
Hence the value of 1

α
+
1

β
− 2αβ is - 15.
OR
Since α, β are the zeros of the polynomial f(x) = x2 - 5x + k.
Compare f(x) = x2 - 5x + k with ax2 + bx + c.
So, a = 1 , b = -5 and c = k
(−5)
α + β = −
1
=5
k
αβ = = k
1

Given, α − β = 1
Now, (α + β) = (α − β) 2 2
+ 4αβ

⇒ (5)2 = (1)2 + 4k
⇒ 25 = 1 + 4k

⇒ 4k = 24

3/6
All the best
⇒ k=6
Hence the value of k is 6.
15. We have
217x + 131y = 913 ..........(i)
131x + 217y = 827 ...........(ii)
Adding equations (i) and (ii), we get
(217x + 131y) + (131x + 217y) = 913 + 827
217x + 131y + 131x + 217y = 1740
348x + 348y = 1740
⇒ x + y = 5 .........(iii)

Subtracting equation (ii) from equation (i), we get


(217x + 131y) - (131x + 217y) = 913 - 827
⇒ 217x + 131y - 131x - 217y = 86
⇒ 86x - 86y = 86
⇒ x - y = 1 .......... (iv)
Adding equation (iii) and (iv), we get
(x + y) + (x - y) = 5 + 1
⇒x+y+x-y=6
⇒ 2x = 6
⇒x=3
Putting x = 3 in equation (iii), we get y = 2.
Hence, x= 3 and y = 2 is the solution of the given system of equations.
16. Sol : Let the required number be x and x + 3. Then,
according to given question we have,
x× (x + 3) = 504
⇒ x2 + 3x = 504
⇒ x2 + 3x - 504 = 0
⇒ x2 + 24x - 21x - 504 = 0
⇒ x(x + 24) - 21(x + 24) = 0

⇒ (x + 24)(x - 21) = 0

⇒ x + 24 = 0 or x - 21 = 0
⇒ x = - 24 or x = 21
Case I: When x = -24
∴ x + 3 = -24 + 3 = -21

Case II: When x = 21


∴ x + 3 = 21 + 3 = 24
Hence, the numbers are -21, -24 or 21, 24.
Section D
17. We have to prove that √5 + √7 is irrational number
– –
Let us assume that √5 + √7 is a rational number
– – a
so √5 + √7 = b
(a and b are integer, b is not equal to 0)
– a –
√5 = b
-
√7 = integer/integer - rational = rational
Since a,b and 5 are integers,

This shows that √5 is rational

But this contradicts the fact that √5 is irrational
Thus our Assumption is wrong
– –
Hence √5 + √7 is irrational
18. Let the number of rows be n.
A.P. formed is 22, 21, 20, 19, ...
Here, a = 22, d = -1 Sn = 250
∴ 250 =
n
[44 + (n − 1)(−1)]
2

⇒ n2 - 45n + 500 = 0

4/6
All the best
⇒ (n - 25)(n - 20) = 0
n ≠ 25 ∴ n = 20
logs in top row = a20 = 22 + 19(-1) = 3
OR
Given that, a = 2, d = 8 and Sn = 90.
As, Sn= n

2
[2a + (n − 1)d]

n
90 = [4 + (n − 1)8]
2

90 = n[2 + (n - 1)4]
90 = n[2 + 4n - 4]
90 = n(4n - 2) = 4n2 - 2n
4n2 - 2n - 90 = 0
4n2 - 20n + 18n - 90= 0
4n(n - 5) + 18(n - 5) = 0
(n - 5)(4n + 18) = 0
18 −9
Either n = 5 or n = − 4
=
2

However, n can neither be negative nor fractional.


Therefore, n = 5
an = a + (n - 1)d
a5 = 2 + (5 - 1)8
= 2 + 4(8)
= 2 + 32 = 34
19. Let A(0, -2), B(3,1), C(0,4) and D(-3,1) be the angular points of quad. ABCD

Now,
−−−−−−−−−−−−−− − −−−− −−− −− −−− − −− –
2 2 2 2
AB = √(3 − 0) + (1 + 2) = √(3) + (3) = √9 + 9 = √18 = 3√2 units
−−−−−−−−−−−−−− − −−−−−−−−− − −−− − −− –
2 2 2 2
BC = √(0 − 3) + (4 − 1) = √(−3) + (3) = √9 + 9 = √18 = 3√2 unit
−−−−−−−−−−−−−−− − −−−−−−−−−− − −−−− −− –
2 2 2 2
C D = √(−3 − 0) + (1 − 4) = √(−3) + (−3) = √9 + 9 = √18 = 3√2 unit
−−−−−−−−−−−−−−− − −−−−−−−−− − −−−− −− –
2 2 2 2
DA = √(0 + 3) + (−2 − 1) = √(3) + (−3) √9 + 9 = √18 = 3√2 unit

Thus, AB = BC = CD = DA
−−−−−−−−−−−−−− − −−−
2 2 2
Diag. AC = √(0 − 0) + (4 + 2) = √(6) = 6 units
− −−−−−−−−−−−−−− − − −−−−
Diag. 2 2 2
BD = √(−3 − 3) + (1 − 1) = √(−6) = 6units

∴ Diag. AC= Diag. BD

Thus, ABCD is a quadrilateral in which all sides are equal and the diagonals are equal
Hence, quadrilateral ABCD is a square
OR
Let the point P ( 1

2
, y) divides the line segment joining the points
A(3, -5) and B(-7, 9) in the ratio k:1.
Then, by section formula,
k×(−7)+1×3 k×9+1×(−5)
Coordinates of P = (
k+1
,
k+1
)

−7k+3 9k−5
= ( , )
k+1 k+1

1
Given, coordinates of P = (
2
, y)

−7k+3 1
∴ =
k+1 2

⇒ -14k + 6 = k + 1
⇒ 15k = 5

5/6
All the best
1
⇒ k =
3

So, the required ratio is 1:3.


9k−5
Also, k+1
= y

1
9× −5
3
⇒ = y
1
+1
3

3−5
⇒ = y
4/3

−6 −3
⇒ y = =
4 2

6/6
All the best

You might also like